Keanekaragaman Jenis Ikan di Hulu Sungai Cikaniki Taman Nasional Gunung Halimun, Jawa Barat - Moh. Rasyid Ridho; Enggar Patriono; Agus Hadiat Tjakrawidjaja (Faculty of Mathtmatics and Natural Sciences, 2003)
The objective of the rearch was to collect information about fish species diversity in upper end of Cikanini River in Gunung Halimun National Park (GHNP), for conservation that is suitable with the status of GHNP a a conservation area in West Java. The research had been conducted in the upper end of Cikanini River, in Citalahab and Cilanggar Village areas during September 1999. The research used survey method. The catching of fish was done from down stream to upper end of Cikanini River wirh difference kinds of sampling method. The result of the research was 9 fish species that had been identified. There was 33.3% of fish species greater than the result of previous research. Fish spesies was dominated by Rasbora aprotaenia. Difference kinds of sampling method are inclined to catch difference fish pecimens. Sampling method using seine net is inclined to catch more specimens. Sampling method using Derris is inclined to catch all species of fish that exist in the fish habitat; however, the number of specimens is lesser than sampling method using seine net. Sampling methods using push net and electric fishing result in a very effective catching in location with rapid current in the middle of river.